EXPERIMENTAL INVESTIGATION OF EFFERVESCENT ATOMIZATION, PART II: INTERNAL FLOW AND SPRAY CHARACTERIZATION WITH NOVEL DARPA SUBOFF AFTERBODY STREAMLINE AERATOR - Niland, Andrew; Santhosh R.; Marsh, Richard; Bowen, Philip (Begell House Inc., 2022)
This experimental work reports, for the first time, observations of an internal flow field involving a DARPA SUBOFF afterbody design aerator body in an inside-out type of effervescent atomizer. The effect of operating parameters like air-to-liquid ratio (ALR), operating pressure, aerator orifice diameter, aeration area, and mixing chamber diameter on internal flow within the effervescent atomizer is studied. The effect of increasing ALR on the internal flow is quantified by identifying different gas injection mechanisms at the aerator orifice (into the mixing chamber) and two-phase mixing chamber flow regimes using high-speed shadowgraphy. In particular, it is observed that as ALR is systematically increased, the gas injection mechanism transits in the following sequence: single bubbling, pulsed bubbling, elongated jetting, atomized jetting, and evacuated chamber. The range of ALRs within which these mechanisms are observed are employed to draw up a flow regime map. Similar analysis on two-phase mixing chamber flow regimes yielded a corresponding regime map for internal two-phase stabilized flow in the mixing chamber. The flow regime transited from bubbly flow, to slug flow, to churn flow, and finally to annular flow as the ALR was increased. The spray characteristics (size and velocity) at the nozzle exit are reported using phase Doppler anemometry measurements. It is observed that dense-bubbly and bubbly-slug flow regimes produce stable sprays with droplet sizes in the range of 50-80 µm in the range of 0.25%-1.50% ALR.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: aerator; DARPA SUBOFF afterbody streamlined aerator; effervescent atomization; gas injection regime; internal flow regimes; mixing chamber design; Atomization; Bubble formation; Orifices; Spray nozzles; Two phase flow; Atomization; Bubble formation; Orifices; Spray nozzles; Two phase flow; Chamber design